Planning an implementation science training program for advanced practice registered nurses. - Hebert, Sharisse; Gaines, Chloe; Benjamin-Garner, Ruby; Moore, Jerrel (JBI Evidence Implementation, 2023)
Background: A gap exists between scientific discovery and implementation and adoption of research findings in healthcare and public health practice. This gap is due to the fact that research on treatment efficacy and safety in clinical trials ends prematurely with the publication of results, leaving a lack of knowledge of treatment effectiveness in real-world clinical and community settings. Comparative effectiveness research (CER) can facilitate the translation of research findings, reducing the gap between discovery and adoption into practice. Getting CER findings to patients and healthcare providers requires efforts to disseminate and train providers to successfully implement and sustain change in the healthcare setting. Advanced practice registered nurses (APRNs) are instrumental in the implementation of evidence-based research in primary care settings and an important group to target for the dissemination of research findings. There are numerous implementation training programs, but none focus specifically on APRNs. Objective: The objective of this article is to describe the infrastructure established to develop a 3-day implementation training program for APRNs and an implementation support system. Method: A description of the processes and strategies is provided, including stakeholder engagement through focus groups and the formation of a multistakeholder program planning advisory team, which includes APRNs, organization leaders, and patients. The program also includes curriculum development and program planning as well as the development of an implementation toolkit. Results: Stakeholders were instrumental in shaping the implementation training program, including the content of the curriculum and the program agenda. In addition, the unique perspective of each stakeholder group contributed to the selection of the CER findings disseminated through the intensive training program. Conclusion: It is important that strategies to address the lack of implementation training opportunities for APRNs be discussed and disseminated within the healthcare community. This article discusses the plan to address implementation training for APRNs through the development of an implementation curriculum and toolkit for APRNs.